The Partner at Home: Psychoeducation and Spouses of Public Safety Personnel - Jackson-Monroe, William (Université d'Ottawa | University of Ottawa, 2025)
An online survey conducted by Carleton and colleagues (2018a) from 2016-2017 revealed that 44% of public safety personnel (PSP) screened positive for clinically significant symptoms of mental health disorders. PSPs, including law enforcement officers, paramedics, and firefighters, are more likely to experience mental health concerns than the general population in Canada (Carleton et al., 2018a). When PSP do seek mental health support, they are most likely to seek support from their spouse or significant other (SSO) and less likely to seek professional support from their organization despite services being at their disposal (Carleton et al., 2020; Henry et al., 2023; O’Toole et al., 2022). This qualitative study, involving interviews with 12 SSOs of PSP, aims to explore SSOs’ experiences in providing support, appraisals of psychoeducation received, and suggestions for improvement. While a significant proportion (50%) of participants shared experiences of secondary traumatic stress, 83% (n =10) reported not having experienced formal psychoeducation/PFA training. SSOs perceived that PSP rely heavily on informal support systems, highlighting the need for targeted psychoeducation programs to enhance mental health outcomes for both PSPs and their SSOs. Administering proactive psychoeducation may help improve mental health outcomes among both PSPs and their SSOs while also benefiting PSP organizations by having a healthier workforce.
Keywords: public safety personnel (PSP); spouse or significant other (SSO); psychoeducation; psychological first aid (PFA); potentially traumatic event (PTE); secondary traumatic stress (STS); occupational stress injury (OSI)